Kønslige narrativer i performancekunsten: En udforskning af flydende kønsidentiteter i performancekunsten med perspektiver fra tre queer kunstnere - Østengaard-Sejersen, Maria Louise (Culture and History: Student Research Papers, 2025)
This article examines the role of performance art in redefining gender identities through an analysis of the works of three queer artists: Justin Shoulder, Kristoffer Raasted, and Stine Kloster. By deconstructing established gender norms and presenting fluid expressions of gender, these artists illuminate how performance art can generate new narratives and challenge traditional conceptions of gender. The article focuses on the capacity of performance art to promote cultural diversity and discusses its contribution to a deeper understanding of gender as a dynamic and mutable construct. This approach demonstrates how performance art serves as a platform for cultural dialogue and transformation.